1994
DOI: 10.1073/pnas.91.26.12467
|View full text |Cite
|
Sign up to set email alerts
|

Visual motion induces synchronous oscillations in turtle visual cortex.

Abstract: In mammalian brains, multielectrode recordings during sensory stimulation have revealed oscillations in different cortical areas that are transiently synchronous. These synchronizations have been hypothesized to support integration of sensory information or represent the operation of attentional mechanisms, but their stimulus requirements and prevalence are still unclear. Here I report an analogous synchronization in a reptilian cortex induced by moving visual stimuli. The synchronization, as measured by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…But one may take this a step further and suggest that contours are actually propagated in the nervous system. This may take place in the form of traveling waves, which have been observed in salamander retina (Jacobs and Werblin 1998) and in primary visual cortex of monkeys and turtles (Grinvald et al 1994;Prechtl 1994;Prechtl et al 1997Prechtl et al , 2000Bringuier et al 1997;Senseman 1999). Most of these described waves are slow (millimeters/seconds) and may suffice, for example, to explain learning processes like the establishment of the CPF (although the turtle cortex does not have orientation columns).…”
Section: Biological Interpretationmentioning
confidence: 93%
“…But one may take this a step further and suggest that contours are actually propagated in the nervous system. This may take place in the form of traveling waves, which have been observed in salamander retina (Jacobs and Werblin 1998) and in primary visual cortex of monkeys and turtles (Grinvald et al 1994;Prechtl 1994;Prechtl et al 1997Prechtl et al , 2000Bringuier et al 1997;Senseman 1999). Most of these described waves are slow (millimeters/seconds) and may suffice, for example, to explain learning processes like the establishment of the CPF (although the turtle cortex does not have orientation columns).…”
Section: Biological Interpretationmentioning
confidence: 93%
“…Also Roelfsma et al (1997) in their research show that the cats waiting for a stimulus related to reward conscientiously showed strong Gamma synchrony. Also other animal studies have shown that Gamma synchrony predominantly is augmented by selective attention that augments the perception and representation of relevant stimuli (Prechtl, 1994).…”
Section: Gamma Activity and Brain Functionsmentioning
confidence: 97%
“…It has been observed in mammals, amphibians, and insects [29,41,42]. It has been measured in the monkey motor cortex [43] and across different hemispheres of the brain in the visual cortices of cats [44].…”
Section: Biologically Inspired Neural Oscillatorsmentioning
confidence: 99%